Relations between ejection fraction and ventricular volume, and their alteration by chronic beta-blockade. - Kerkhof, P L (1981)
This study describes the newly discovered relation between ejection fraction and end-systolic volume index (ESVI) of the left ventricle as obtained by angiography at the time of cardiac catheterisation. Linear regression analysis shows that ejection fraction (%)=82.0-0.62 ESVI (ml/m2) but the correlation for patients receiving beta-adrenergic blocking drugs is significantly lower compared with the untreated group. Non-linear analysis, applied to cover also the asymptotic range for ejection fraction less than 20%, shows similar results. The good relation between the two indices indicates that the index ejection fraction may derive its clinical importance directly from the more fundamental index end-systolic volume index by virtue of the operation of the beta-adrenergic system on the heart.